Safety and short-term outcomes of endoscopic submucosal dissection for early gastric cancer in elderly patients - Kato, Minoru; Michida, Tomoki; Kusakabe, Akira; Sakai, Ayako; Hibino, Chihiro; Kato, Mina; Tokuda, Yuki; Kawai, Tomoyo; Hamano, Mina; Chiba, Miho; Maeda, Kosaku; Yamamoto, Katsumi; Naito, Masafumi; Ito, Toshifumi (Endoscopy International Open, 2016)
Background and study aims: Endoscopic submucosal dissection (ESD) has become widely accepted as a minimally invasive treatment for early gastric cancer (EGC), and opportunities to use ESD to treat EGC in elderly patients are increasing. The objective of this study was to elucidate the safety and efficacy of ESD in elderly patients.Patients and methods: Between April 2006 and March 2013, a total of 892 patients with EGC were prospectively recruited to undergo ESD according to definite inclusion criteria. The short-term outcomes and incidence of complications in 345 of these patients who were 75 years of age or older (elderly group) were compared with the short-term outcomes and incidence of complications in the remaining 547 patients (non-elderly group). Factors associated with the occurrence of pneumonia and delirium were also investigated.Results: The R0 resection rate did not differ between the two groups (96.2 % in the elderly group vs. 96.7 % in the non-elderly group; P = 0.65). The incidence of pneumonia (7.5 % vs. 1.8 %; P < 0.01) and incidence of delirium (10.1 % vs. 1.1 %; P < 0.01) were significantly higher in the elderly group. The incidence of post-ESD bleeding and incidence of perforation were similar in the two groups. No emergency surgery was required, but one patient in the non-elderly group died of aspiration pneumonia. On multivariate analysis, age 75 years or older, cerebrovascular disease, chronic obstructive pulmonary disease, delirium, and remnant stomach or gastric tube were independent risk factors for pneumonia, and age 75 years or older, diabetes, dementia, and pneumonia were independent risk factors for delirium.Conclusion: ESD for EGC was feasible for elderly patients in good condition. However, pneumonia and delirium may develop more frequently after ESD in elderly patients with co-morbidities.